Analisis Tata Kelola Teknologi Informasi Untuk Meningkatkan Mutu Sumber Daya Manusia Pada Dinas Tenaga Kerja Dan Transmigrasi Provinsi Nusa Tenggara Barat Menggunakan Framework COBIT 5.0 - Azmi Yunda Chairani; Royana Afwani; Sri Endang Anjawarni (Journal of Computer Science and Informatics Engineering (J-Cosine), 2019)
The West Nusa Tenggara Department of Manpower and Transmigration (DISNAKERTRANS NTB) is one of the government organizations that assists the Governor of West Nusa Tenggara on labor and transmigration issues. IT governance in a company or organization is very necessary to harmonize organizational goals and strategies. With the problems found regarding to the resources both human resources and IT resources at DISNAKERTRANS NTB. Therefore, the purpose of this study is to determine the capability level of IT governance at DISNAKERTRANS NTB using the COBIT 5 framework by focusing on APO01 subdomains: Manage IT management frameworks, and APO07: Manage human resources. From the research results, the average capability level for the current conditions shows that APO01 and APO07 are at level 2. While the average capability level of the expected condition, shows that APO01 and APO07 are at level 4.to increase the current level, some recommendations are given to be considered by DISNAKERTRANS NTB in drafting the policies relating to the APO01 and APO07 processes. Keywords: IT governance, capability level, COBIT 5.0, APO01, APO07.